2008
DOI: 10.1099/jmm.0.47827-0
|View full text |Cite
|
Sign up to set email alerts
|

Secreted subtilisins of Microsporum canis are involved in adherence of arthroconidia to feline corneocytes

Abstract: Microsporum canis is a pathogenic fungus that causes a superficial cutaneous infection called dermatophytosis, mainly in cats and humans. The mechanisms involved in adherence of M. canis to epidermis have never been investigated. Here, a model was developed to study the adherence of M. canis to feline corneocytes through the use of a reconstructed interfollicular feline epidermis (RFE). In this model, adherence of arthroconidia to RFE was found to be time-dependent, starting at 2 h post-inoculation and still i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 25 publications
1
45
0
5
Order By: Relevance
“…In line with this assumption, previous studies of reconstituted human epithelia infected with C. albi- cans revealed that supplementation of the model with polymorphonuclear leukocytes strongly impaired tissue invasion by this pathogenic yeast (22). In the past, various in vitro models using reconstituted epidermis or skin explants have been established and were also proven successful for the analysis of dermatophytosis (1,2,5,7,19,20,24,26). Nevertheless, the commercially available RHE model, which was employed in the present study for the analysis of A. benhamiae mutants, may further advance the research of dermatophytosis and the identification of basic virulence attributes of dermatophytes.…”
Section: Discussionmentioning
confidence: 69%
“…In line with this assumption, previous studies of reconstituted human epithelia infected with C. albi- cans revealed that supplementation of the model with polymorphonuclear leukocytes strongly impaired tissue invasion by this pathogenic yeast (22). In the past, various in vitro models using reconstituted epidermis or skin explants have been established and were also proven successful for the analysis of dermatophytosis (1,2,5,7,19,20,24,26). Nevertheless, the commercially available RHE model, which was employed in the present study for the analysis of A. benhamiae mutants, may further advance the research of dermatophytosis and the identification of basic virulence attributes of dermatophytes.…”
Section: Discussionmentioning
confidence: 69%
“…Nevertheless, it is clear that an extracellular pH shift is not required for the inhibitory action of UDA on the H6 strain grown on Tween 20 or keratin cultures. Indeed, it is possible that a contact sensing response for fungal growth on Tween 20 or keratin avoids the inhibitory action of UDA (Baldo et al 2008;Kumamoto 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In M. canis, adherence to feline corneocytes was previously found to be reduced by the use of chymostatin, a serine protease inhibitor and by the use of a mixture of two monoclonal antibodies against Sub3. 24 In the pathogenic bacteria Porphyromonas gingivalis and Streptococcus pneumoniae, a membrane-associated dipeptidyl peptidase IV and a surface-associated serine protease named choline-binding protein G, respectively, are involved in adherence. 25,26 Similarly, in the yeast Candida albicans, a family of 10 secreted proteases (Saps) is involved in the adherence and invasion of skin and mucosal surfaces.…”
Section: Discussionmentioning
confidence: 99%